Economic growth and electricity consumption: MS-VAR and MS-Granger causality analysis - Bildirici, Melike E. (WILEY, 2013)
This study estimates the causality relationship between electricity consumption and economic growth by Markov Switching VAR (MS-VAR) method for some emerging countries: Argentina, China, India, Brazil, Mexico, Turkey and South Africa. Knowledge of the direction of causality between electricity consumption and economic growth is of primary importance if appropriate energy policies and energy conservation measures are to be devised. The results from MS- VAR models show that in first, second and third regime, electricity consumption is the Granger cause of the economic growth and economic growth is the Granger cause of the electricity consumption. In sum, we found some evidence of bidirectional Granger causality between the electricity consumption and the economic growth.
Keywords: Business & Economics